Hubungan Pola Asuh Dengan Perilaku Seksual Beresiko Pada Siswa-Siswi di SMA Swasta BW Bekasi : The Relationship Between Parenting Patterns and Risky Sexual Behavior Among Students in Private BW High School in Bekasi - Elisabeth Daryati Isti; Loviga Jagadita (Journal of Nursing Education and Practice, 2022)
Background: Adolescence is a transition period prone to risky sexual behavior due to social and environmental pandemic situations. These conditions need to consider by the parent when caring for their child's developmental. Types of parenting authoritative, permissive, and democratized can influence their good or risky sexual behavior. Objectives: This study aims to identify related parenting patterns with sexual behavior risk in adolescence at SBW high school. Method: This research is a quantitative study with a cross-sectional approach, using a questionnaire via a google form. The study was conducted from December 2020 until January 2021 with 306 respondents in total sampling. Data analysis using Spearman Rho test. Result: The bivariate analysis showed that parenting patterns did not significantly correlate with risky sexual behavior (p-Value 0,864) between male and female students at SBW high school. Conclusion: The conclusion of this study is that researchers can assess of parenting style with the character of sexual behavior without physical contact with adolescents.